2016
DOI: 10.1590/0100-29452016791
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1-Methylcyclopropene on the Biochemical Response and Ripening of ‘Solo’ Papayas

Abstract: abstract-The market demand for tropical fruits has been growing steadily over the past two decades and global papaya production has grown significantly over the last few years. This sector, however, suffers greatly from postharvest losses due to reduced quantity and quality of fruits between harvest and consumption. The use of ethylene inhibitors after harvest could improve the final quality of the fruit to satisfy the consumer and also minimize waste. The physiological and biochemical responses of 'Solo' papa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The consumption of fresh fruits has significantly increased over the last decade [1]. This increase could be due to heightened public awareness of the benefits of fresh food consumption such as providing the body with vitamin A, vitamin C, folate, minerals, dietary fiber, and phytochemicals [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of fresh fruits has significantly increased over the last decade [1]. This increase could be due to heightened public awareness of the benefits of fresh food consumption such as providing the body with vitamin A, vitamin C, folate, minerals, dietary fiber, and phytochemicals [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of 1-MCP on delaying senescence may be attributed to its ability to inhibit ethylene synthesis (SISLER; SEREK, 1997), leading to delayed senescence and maintenance of fruit quality, such as delayed softening or a delay in ripening and other changes which may lead to an increase in the storage life of the fruit (BLANKENSHIP;DOLE, 2003). Asmar et al (2010) submitted papaya fruits (Sunrise Solo) to 1-MCP (270 nL L -1 ) for 0, 12, 18 and 24 h, and then stored them (22 ± 2°C; RH 77% ± 2%) for 8 d. Ohashi et al (2016) found that the use of 1-MCP for fruits increased 'Solo' papaya shelf-life, because of the ability to inhibit ethylene action in tissues, delaying fruit ripening. The 1-MCP-treated fruits showed increased firmness, lower contents of soluble pectin and less activity of the PME enzyme, demonstrating that 1-MCP was effective in delaying the softening of the fruits.…”
Section: Resultsmentioning
confidence: 99%
“…1.0 μl/L 1‐MCP on Rosa sterilis D. shi fruits delayed ascorbic acid depletion, suppressed the respiration rate, and ethylene production rate (Xie et al, 2020). “Solo” papayas ( Carica papaya L.) treated with 1 μl/L 1‐MCP showed a reduction in respiratory rate and ethylene production, as well as better maintenance of the green color of the peel and firmness after 7 days (Ohashi et al, 2016). When minimally processed mangoes were treated with UV radiation and 1‐MCP, 1‐MCP was not effective at preventing browning (de Sousa et al, 2017).…”
Section: Chemical Preservation Methodsmentioning
confidence: 99%